Community sharing: Contextualizing Western research notions of contamination within an Indigenous research paradigm. Issue 1 (17th September 2021) - Allen, Sarah; Held, Suzanne; Milne‐Price, Shauna; McCormick, Alma; Feng, Du; Inouye, Jillian; Schure, Mark; Castille, Dottie; Howe, Rae B.; Pitts, Mikayla; Keene, Shannen; Belone, Lorenda; et al.
Abstract: Báa nnilah is a chronic illness self‐management program designed by and for the Apsáalooke (Crow) community. Arising from a collaboration between an Indigenous nonprofit organization and a university‐based research team, Báa nnilah's development, implementation, and evaluation have been influenced by both Indigenous and Western research paradigms (WRPs). Báa nnilah was evaluated using a randomized wait‐list control group design. In a WRP, contamination, or intervention information shared by the intervention group with the control group, is actively discouraged as it makes ascertaining causality difficult, if not impossible. This approach is not consonant with Apsáalooke cultural values that include the encouragement of sharing helpful information with others, supporting an Indigenous research paradigm's (IRP) goal of benefiting the community. The purpose of this paper is to address contamination and sharing as an area of tension between WRP and IRP. We describe how the concepts of contamination and sharing within Báa nnilah's implementation and evaluation are interpreted differently when viewed from these contrasting paradigms, and set forth a call for greater exploration of Indigenous research approaches for developing, implementing, and evaluating intervention programs in Indigenous communities. (Improving Chronic Illness Management with the Apsáalooke Nation: The Báa nnilah Project.: NCT03036189), ClinicalTrials. gov: NCT03036189). Highlights: Within an Indigenous research paradigm, the purpose of research is to improve people's lives and their community and must be relational. When one contextualizes Western research notions of contamination within an Indigenous research paradigm, sharing helpful information with others takes on a different meaning. We identify a number of ways Indigenous voices and research methods can be amplified within CBPR.